Sensitive determination of copper in water samples using dispersive liquid-liquid microextraction-slotted quartz tube-flame atomic absorption spectrometry - Ozzeybek, Gozde; Erarpat, Sezin; Chormey, Dotse Selali; Firat, Merve; Buyukpinar, Cagdas; Turak, Fatma; Bakirdere, Sezgin (ELSEVIER SCIENCE BV, 2017)
Determination of trace amount of copper in environmental samples is necessary due to its toxic properties and dangers to living organisms. Dispersive liquid-liquid microextraction (DLLME) was coupled with slotted quartz tube (SQT) to lower the detection limit for copper using flame atomic absorption spectrometry (FAAS). Parameters affecting the formation of copper-ligand complex, DLLME efficiency and SQT output were systematically optimized to improve copper detection signal. The SQT-FAAS, DLLME-FAAS and DLLME-SQT-FAAS systems were 2, 42 and 79 times, respectively, more sensitive than the conventional FAAS system. The limit of detection (LOD) and quantitation (LOQ) values obtained for the combined methods (DLLME-SQT-FAAS) were calculated as 0.7 and 2.2 mu g L-1, respectively. The method recorded appreciable recoveries for all samples tested (78%-99%), and experimental results of a certificated references material (EU-L-2) agreed with the certified value. (C) 2017 Published by Elsevier B.V.
Keywords: Copper; Dispersive liquid-liquid microextraction (DLLME); Slotted quartz tube (SQT); Flame atomic absorption spectrometry (FAAS); TRACE AMOUNT; PRECONCENTRATION; EXTRACTION; CADMIUM; LEAD; GENERATION; Chemistry